Melatih keterampilan siswa SMP dalam menggunakan Microsoft Office dan PhET - Hikmawati Hikmawati; Julia Izni Malika; Firda Aprilia Insani; Nur Rahmah; Paramita Suhartanti (Pascasarjana Universitas Mataram, 2021)
Skills in running computer programs are important for students so that they are able to learn and work in accordance with developments in technology, information, and communication. The purpose of this community service activity is to train junior high school students' skills in using Microsoft Office and PhET. This activity was carried out at SMPN 19 Mataram for 8 weeks, starting from September 27 to November 21, 2021. This activity is part of the Campus Teaching Program Batch 2. The methods of implementing the activities are: planning, implementing, and evaluating activities. At the activity planning stage, the team coordinated and discussed with supervisors, subject teachers (ICT and Science), and school principals. At the activity implementation stage, the team trained students in using software applications, namely Microsoft Office and PhET. Applications in Microsoft Office that are chosen to be trained to students are Excel, Word, and PowerPoint. Meanwhile, PhET Simulation taught to students is the topic of Static Electricity. The training schedule for Microsoft Office uses ICT subject time, while for PhET uses Science subject time. At the activity evaluation stage, the team together with the supervisors identify the obstacles experienced and the improvement efforts made every week. The team also coordinated and discussed with ICT subject teachers, science teachers, and school principals about the follow-up plan of the training activities. The training provided by the team on technology adaptation in the form of using software applications has improved the skills of junior high school students in using computer programs, namely Microsoft Office and PhET.